2017
DOI: 10.1177/1010428317694304
|View full text |Cite
|
Sign up to set email alerts
|

CDK9 is a prognostic marker and therapeutic target in pancreatic cancer

Abstract: Despite recent advances in diagnosis and therapy, prognosis of pancreatic cancer still remains very poor. Besides valid prognostic markers, novel therapeutic approaches are urgently needed. The family of cyclin-dependent kinases comprises 20 kinases which contribute to malignancy by promoting proliferation, migration, invasion, and apoptotic resistance of cancer cells. In this work, we investigated the role of CDK9 in pancreatic cancer. Immunohistochemical analysis of CDK9 expression in tumor and normal tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 38 publications
8
36
0
Order By: Relevance
“…Further analysis revealed that a high level of CDK9 expression was associated with a worse prognosis for sarcoma patients, whereas patients with lower CDK9 expression had a better prognosis intern of overall survival. Therefore, as reported for other cancer types, our findings confirm that the overexpression of CDK9 is associated with a poor patient prognosis . The function of CDK9 was also evaluated in vitro and ex vivo, with results showing that inhibition of CDK9 suppresses cell growth and proliferation, spheroid formation, and motility, while inducing apoptosis in synovial sarcoma cells.…”
Section: Discussionsupporting
confidence: 89%
“…Further analysis revealed that a high level of CDK9 expression was associated with a worse prognosis for sarcoma patients, whereas patients with lower CDK9 expression had a better prognosis intern of overall survival. Therefore, as reported for other cancer types, our findings confirm that the overexpression of CDK9 is associated with a poor patient prognosis . The function of CDK9 was also evaluated in vitro and ex vivo, with results showing that inhibition of CDK9 suppresses cell growth and proliferation, spheroid formation, and motility, while inducing apoptosis in synovial sarcoma cells.…”
Section: Discussionsupporting
confidence: 89%
“…Given that low CDK9 expression leads to increased spontaneous DNA damage and genetic instability, we speculate that patients with residual breast tumors with low CDK9 expression may have more aggressive disease and thus poorer prognoses. This paradoxical observation is in contrast to another study investigating CDK9 expression in patients with de novo pancreatic adenocarcinoma tumors, which showed that high CDK9 expression has worse clinical outcome [ 21 ] as well as its current investigation as a therapeutic target for cancer treatment [ 22 25 ].…”
Section: Discussionmentioning
confidence: 60%
“…Similarly, among the most advanced CDK4 and CDK6 inhibitors, purinomimetics abemaciclib (LY2835219) [ 22 , 23 ] and ribociclib (LEE011) ( Figure 1 ) [ 23 , 48 ] showed to be potent CDK9 inhibitors. In addition, the therapeutic potential of selective CDK inhibition on pancreatic cancer cells was revealed by other structurally related small molecule CDK inhibitor, dinaciclib (SCH727965) ( Figure 1 ) [ 21 , 49 ]. Furthermore, PASS analysis also revealed that some of selected compounds could potentially inhibit p38 MAP kinase with higher (compound 6b ) or lower probability (compound 4g ) ( Tables S4–S6 ).…”
Section: Resultsmentioning
confidence: 99%